Gestión de errores del sistema de facturación y reserva del Hotel Jared de la Parroquia Ricaurte. - Barvera Quinto, Erick Ambrocio (2022)
Service companies are concerned about critical activities that are most prone to errors, because when they do occur, they require time and money to fix. Some of the most critical operations are billing. In some situations there are problems with the final document, usually due to errors of use, changes and defects, etc. The purpose of this case study is to know what is the diagnosis and description of the error management of the billing and reservation system of the JARED hotel in the Ricaurte parish. Electronic invoicing systems support all physical and digital receipts. One of the characteristics of billing systems is that they significantly reduce the monthly cost of office supplies and the distribution time per issued document. The electronic invoice complies with the legal requirements of traditional receipts and guarantees, among other things, the authenticity of the origin and the accuracy of its content, generating greater legal certainty and reducing the risk of fraud and tax evasion. This results in slowness and fiscal ignorance that leads companies to enter incorrect information on the invoice, which, in addition to delaying accounting, can also cause a series of problems in the tax administration. As the main conclusion of this case study, I can say that after analyzing the current state of the Hotel Jared and carrying out the pertinent studies, the result obtained is the dissatisfaction of the tourists, that is, they are not satisfied with the services that are currently offered. they provide. of this hotel company for not meeting their expectations, needs and comfort for a pleasant stay.